Trabalho, logo existo: um estudo sobre a dinâmica dos sentidos do trabalho ao longo da trajetória profissional - Moresco, Michel Augusto (2019)
Work exerts a central role in the life of man; it is in their occupational and professional activity that the contemporary man spends most of their life and it is through work that they acquire identity, subsistence and prosperity. Therefore, the individual seeks to relate work to aspects that contribute to give meaning to this activity, like coherence, usefulness, pleasure, acknowledgement and identity. Thus, the present research aimed to studying how the dynamics of the meanings of work happens throughout the career path for managers of a Brazilian financial institution. Six branch managers were interviewed, four who are still in their function, and other two who retired. It is a research of qualitative nature, which provided a deep immersion in the organizational context and the history of each participant, and enabled the capturing of elements and the building of richer and clearer results. The choice was the application of narrative interviews, in an individual format was adapted, aiming at the in-depth of the interviewees‟ experiences. The narrative interviews showed that workers seek an activity which provides personal and professional satisfaction; which has clear and realistic goals; which contributes to society and to the organization; which allows the individual to build social interactions that enable professional growth and learning; which allows them to feel worthy; which provides security and autonomy. Moreover, the interviewed managers‟ narratives led the research to a plot of unique labour experiences, filled with uncertainties, inaccuracies and contradictions as in every path, where the meanings of work adjust to the experienced context and to the individuals‟ perspectives. Thus, inasmuch as the career paths develop, the meanings change. If, at the start of the career, the meanings of work were merely the source of subsistence and independence, with the passing of time, as work becomes multifaceted, emerging as the central pillar in the individual‟s life, new meanings are incorporated, such as those related to development, satisfaction, acknowledgement, usefulness and interpersonal relations.